Sequential Shift Absolute Phase Aberration Calibration in Digital Holographic Phase Imaging Based on Chebyshev Polynomials Fitting - Weilin He; Jiantai Dou; Zhongming Yang; Zhenhua Liu; Zhaojun Liu (IEEE Photonics Journal, 2020)
We propose a novel absolute calibrate method for digital holographic microscopy with the sequential shift method using Chebyshev polynomials. We separate the object phase and the aberrations by sequential shifting the sample twice in vertical plane of the optical axis. The aberrations phase is then calculated using the high order Chebyshev polynomials. The correct phase is obtained by subtracting the aberrations from the original phase containing the aberration. This method can compensate for the complex aberrations including high-order aberrations without changing the traditional optical system. Meanwhile, it can effectively protect the medium and high frequency information of the specimen in the phase image. Numerical simulation and experimental results demonstrate the availability and advantages of the absolute calibrate method.